Better global and cognitive functioning in choreatic versus hypokinetic‐rigid Huntington's disease. Issue 8 (14th March 2013) - Hart, Ellen P.; Marinus, Johan; Burgunder, Jean‐Marc; Bentivoglio, Anna Rita; Craufurd, David; Reilmann, Ralf; Saft, Carsten; Roos, Raymund A.C.; ,
<x xml:space="preserve">Abstract</x> Background Understanding the relation between predominantly choreatic and hypokinetic‐rigid motor subtypes and cognitive and general functioning may contribute to knowledge about different motor phenotypes in Huntington's disease. Methods In the European Huntington's Disease Network Registry study, 1882 subjects were classified as being predominantly choreatic (n = 528) or hypokinetic‐rigid (n = 432), according to their scores on items of the total motor score a priori labeled as choreatic or hypokinetic‐rigid; the other 922 patients were of a mixed type. The relationship between motor type and cognitive (verbal fluency, symbol digit modalities, Stroop color, word and interference tests) and functional (total functional capacity) capacity was investigated using multiple linear regression. Results Motor subtype contributed significantly to the total functional capacity score (partial r2: 7.8%; P < .001) and to the 5 cognitive scores (partial r2 ranged from 2.0% to 8.4%; all P < .001). Conclusions Patients with a predominantly choreatic motor phenotype performing better in all areas than patients with a hypokinetic‐rigid motor phenotype. © 2013 Movement Disorder Society